Implementasi Metode TOPSIS pada Sistem Rekomendasi Tempat Wisata Belanja di Kota Malang Berbasis Lokasi - Muhammad Robby Dharmawan; Ratih Kartika Dewi; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The tourism sector is an industry that is favored by countries in the world. In 2017 foreign tourist visits coming to Indonesia amounted to 14 million visits which increased by 20% compared to 2016 which reached 11 million visits. In traveling, tourists tend to do shopping so that shopping tourism locations appear. Malang City is a city located in East Java province which has a variety of various tourist locations to be visited including shopping attractions. The number of shopping attractions in the city of Malang often makes tourists confused to have a shopping destination. At present, information about shopping places in Malang is still using the web which cannot provide recommendations to tourists. This study offers a recommendation system for shopping tourism in Malang that uses the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method because the best alternative results are alternative ranking which has the closest distance from the distance of the positive ideal solution and farthest distance is the ideal negative solution by using criteria such as rating, number of reviews, operational time, and distance. Functional testing on the system results in 100% validity. Non-functional testing on the system uses algorithm validation and usability. From the algorithm validation test, the results of the system output comparison with manual calculations have a validity of 100%. From usability testing by distributing 30 questionnaires with 25 questions, the end user satisfaction rate was 88.47%.